Rhinella mirandaribeiroi (Gallardo, 1965) (Amphibia: Anura: Bufonidae): Distribution extension and new state record - de Pina, Ligia Ferracine; Morais, Alessandro R.; Prado, Cynthia P. A. [UNESP] (Pensoft Publishers, 2015)
Rhinella mirandaribeiroi is widely distributed in the Cerrado domain and Cerrado enclaves in the Amazon forest, occurring also at the ecotone between this domain and surrounding formations. Here, we provide the first species record for the state of São Paulo, municipality of São Joaquim da Barra, northeast of the state. Additionally, we also provide a distribution map. This new record fills a gap in the species´ distribution in southeastern Brazil.
Keywords: Geographic distribution map; Rhinella granulosa species group; Sapucaí-Mirim/Grande River basin; São Paulo